2018
DOI: 10.1111/jorc.12241
|View full text |Cite
|
Sign up to set email alerts
|

Developing and pilot testing a shared decision‐making intervention for dialysis choice

Abstract: An intervention based on shared decision-making supported by decision aids seemed to increase the number of patients choosing home dialysis. The SDM Q9 and DQM were feasible evaluation tools. Further research is needed to gain insight into the patients' experiences of involvement and the implications for their choice of dialysis modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…A detailed description of the SDM-DC intervention can be found in the online supplementary material. The pilot test confirmed that SDM-DC was useful in encounters between individual patients and a dialysis coordinator at a Danish university hospital, but that further research was needed to gain insight into patients’ experiences of involvement and the implications for their choice of dialysis mode 10…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…A detailed description of the SDM-DC intervention can be found in the online supplementary material. The pilot test confirmed that SDM-DC was useful in encounters between individual patients and a dialysis coordinator at a Danish university hospital, but that further research was needed to gain insight into patients’ experiences of involvement and the implications for their choice of dialysis mode 10…”
Section: Introductionmentioning
confidence: 79%
“…The decision was experienced as being their own was a significant finding, which demonstrates that the patients experienced SDM-DC as involving them in the decision-making process. The SDM-DC pilot test predicted this finding, because some of the patients did not experience the decision as a shared decision, but their own decision 10. Due to the age of the patient group, this finding was surprising when compared with a study focusing on the involvement of the over-65 age group 39.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2018, nine studies evaluating interventions based on SDM in dialysis choice were identified [7], but few had been rigorously evaluated in clinical practice. In fact, none of these studies evaluated the SDM process or the decisional outcomes.…”
Section: Introductionmentioning
confidence: 99%